2001
DOI: 10.1002/jsc.546
|View full text |Cite
|
Sign up to set email alerts
|

Taking risk in joint ventures: whose throw of the dice?

Abstract: The development of key partnerships between innovative small and medium-sized enterprises (SMEs) and larger organizations is a primary strategic consideration. The level of risk involved can often mean that smaller firms are placed in highly vulnerable positions when attempting to develop a product, process or service.• Risk may be related to a wide range of influences including asymmetric resource allocation, the perception and framing of problems and the building of trust and commitment. The smaller organiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…At the level of the firm, this literature examines both the characteristics of the small business as well as those of the partnering firm. For example, small firms are more likely to form cooperative arrangements than larger firms (Shan 1990), but in relationships between businesses of unequal sizes, the smaller firm is often asked to take on the higher level of risk (Sulej, Stewart, and Keogh 2001). Also, businesses with significant inventions but lacking commercial, technical, and social capital are more likely to seek partners (Ahuja 2000).…”
Section: Gibson Andmentioning
confidence: 99%
See 1 more Smart Citation
“…At the level of the firm, this literature examines both the characteristics of the small business as well as those of the partnering firm. For example, small firms are more likely to form cooperative arrangements than larger firms (Shan 1990), but in relationships between businesses of unequal sizes, the smaller firm is often asked to take on the higher level of risk (Sulej, Stewart, and Keogh 2001). Also, businesses with significant inventions but lacking commercial, technical, and social capital are more likely to seek partners (Ahuja 2000).…”
Section: Gibson Andmentioning
confidence: 99%
“…External factors such as environmental conditions of uncertainty (Weaver, Dickson, and Gibson 1997) and market conditions of high competition (Eisenhardt and Schoonhoven 1996) force small companies to look for larger partners. Often though, the larger partners have more power and control and can force smaller businesses to take on more of the risk (Sulej, Stewart, and Keogh 2001). If the partners have too much power and are too bureaucratic, small businesses may be unwilling to form a relationship with them (Rothwell and Dodgson 1991) as they risk losing control of their own business (Gomes-Casseres 1997).…”
Section: Bringing It Together-future Directions For Researchmentioning
confidence: 99%
“…This risk is an important consideration for innovative SMEs as they tend to have limited resources and must be careful to apply them in an effective way in order to maximize their potential gains. Sulej (2001) suggested the use of scenario planning. However, their research suggested that unlike large organizations, few innovative SMEs currently make use of techniques such as scenario planning in any formal way.…”
Section: Frederick a Frostmentioning
confidence: 99%
“…Rothaermel and Deeds (2004) argue that due to their initially weak bargaining position, new technology ventures tend to cede a disproportional amount of control rights to the financier of the R&D alliance. The larger partners have more power and control and can force smaller ones to take on more of the risk (Sulej, Stewart, and Keogh 2001). Also, increased dependency on a dominant partner (overdependency) will limit the flexibility.…”
mentioning
confidence: 99%